Et naivt forsøg på forståelse – Dansk Samling og Tyskland - Øhrgaard, Per (Folia Scandinavica Posnaniensia, 2016)
In the 1930s, one of several small anti-parliamentarian, more or less authoritarian movements in Denmark was ”Dansk Samling” (Danish Unity, see note 3), by its critics labeled as fascist or even nazi, in its self-understanding above all Christian and national and thus strongly opposed to any import of German ideology. In 1938, some of its members attended a meeting in Lübeck, and later that same year the movement’s periodical published ”greetings to Germany” – a rather naive attempt at reaching a dialogue, but still without giving in on crucial matters.